SnS2 nanoflakes for efficient humidity and alcohol sensing at room temperature - Bharatula, Lakshmi Deepika; Erande, Manisha B.; Mulla, Imtiaz S.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report a one step facile hydrothermal synthesis of layered SnS2 nanoflakes. The as-synthesized nanosheets are characterized using X-ray diffraction, Raman spectroscopy and Transmission Electron Microscopy (TEM). The humidity sensing behavior of SnS2 nanoflake sensor device were investigated in the range of 11-97% of relative humidity (RH) at room temperature. The response time of similar to 85 s and recovery time of similar to 6 s were observed for the SnS2 nanoflake based humidity sensor. A maximum sensitivity of 11.300% is recorded. We also investigate the SnS2 nanoflake based alcohol sensing properties towards methanol, ethanol and iso-propyl alcohol. An exclusive selectivity towards methanol with a response of 1580 is shown as compared to other analytes. The response time of similar to 67 s and recovery time of just 5 s were observed for the SnS2 nanoflake based methanol sensor.